The Variability of Transcoding and Transformations of the Eponym Proprial Component in the Interlingual Transition - Kiyko, Svitlana; Stegnitska, Liubov; Shkolna, Natalia (My University, 2023)
Choosing the standard of eponym, which is an international layer of vocabulary, it is necessary to comply with criteria such as consistency, accuracy, uniqueness, reflexivity, the absence of an intermediary language, normativity, etc. But despite its versatility, when transferring an eponym from one language to another, its proprial component is often subject to certain changes. Such changes arise due to the variability of transcoding and transformation of the proper name, caused not only by the features of the recipient’s language, but also by the anthropocentric character of the lexicography, which relies on certain experience and existing developments. The transcoding itself is often used when translating international realities; it can convey content as briefly as possible preserving the form. The main methods of proper name transcoding are transliteration and transcription. In addition to transliteration and transcription, eponyms undergo mixed and adaptive transcoding. As for transformations, such interlanguage transformations of the proper name can be made using graphic, grammatical and phonetic transformations. During the transition of proprial vocabulary from one language to another, such graphic transformations as the variable use of apostrophe, hyphen, capitalization, and diacritical marks are traced. Grammatical transformations are present in the form of permutations, substitutions, addition, deletions, and complex transformations. Manifestations of phonetic transformations occur by assimilation, dissimilation, epenthesis, dieresis, elision, palatalization, haplology and substitution. Lexical transformations are a quite rare phenomenon, and still can be traced in the form of generalization and substantiation, which are inherent in the main appellative component of eponym. Whereas, demetaphorization, interhyponymic transformation (replacement of realia) are possible manifestations of lexical transformations of the proprial component.
Keywords: eponym; variability; transcoding; transformations; interlingual transition